Chemical constituents and biological activities of essential oil from chempaka (Michelia alba de candolle) - Abu Shah, Nor'aishah (2013)
Malaysia is one of the twelfth mega-diversity countries in the world with a lot of colourful and aromatic flowers flowering throughout the year. Unfortunately many plant species are not fully exploited towards perfume production. Michelia alba, an aromatic plant with fascinating flower odour, has long been used as fragrance in perfume and cosmetics products. However, there is still shortage of information on the chemical profile their pharmacognosy values. The flower only budding mostly during rainy season, concurrently with shoots formation. Furthermore, this local plant is hardly produce fruit or seeds due to pollen shortage and exhibit low efficiency in conventional propagation. This study was carried out to profile the chemical and biological properties of the essential oils in fresh M. alba flowers and leaves and establish essential oil production in its callus cultures. The chemical compositions of the essential oils of M. alba flowers (from white bud to full bloom flower) and the leaves were determined using gas chromatography-mass spectrometry (GC-MS) techniques. Approximately 100 compounds were detected and 30 were chromatographically identified. Linalool was found to be dominant in the leaf essential oils at 76.6% while it constituted 67.1% in the stage 8 flower. Other major chemical constituents detected in the leaf oil were farnesol (5.5%), β-elemen (3.7%) and nerolidol (2.2%). Other abundant chemical components in most of the flower stages were 2-methyl-methyl-ester-butanoic acid, phenol, caryophyllene,phenyl ethyl alcohol, ocimene and germacrene D. The compositions of the essential oils in different parts of the flower revealed that the highest percentage of linalool were from gynoecium, stamen and tepal at 74.5%, 74.4% and 38.8%, respectively. Other major compounds found were 2-methyl-butanoic acid and 2-methyl-methylester-butanoic acid. The essential oils from the fresh flowers and leaves of M. alba were specifically extracted to further test their effects towards growth inhibition of different pathogenic bacteria and fungi using disc diffusion assay. Two kind solvents of flower and leaf extracts were used to examine the effect of extraction solvents with different polarities on biological activities. Most of the extracts from different solvents used inhibit the growth of all the bacteria tested. The extracts showed better antibacterial effects on most of the tested bacteria with lower MIC values ranging from 1.25 to 10.00 μl/ml. The least inhibited bacteria was Pseudomonas aeroginosa, effective only with leaf essential oil extracted in dichloromethane (MIC value 10.00 μl/ml). All Gram-negative bacteria tested were more resistant compared to the Grampositive bacteria. Candida albicans was found to be more susceptible to the leaf extract, while Fusarium oxysporium was more susceptible to the dichloromethane flower extract. Overall, the results showed that the leaf gave better inhibitory effect from dichloromethane extract (DL) and the flower from n-pentane extract (PF),consistent with the higher percentage of linalool in the leaf (DL: 76.6%) and the flower (PF: 63.2%). The antioxidant activity of the fresh flowers and leaves extracted with dichloromethane and n-pentane were also investigated with three different established methods: the conjugate diene method, the 2,2’-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging method and -carotene bleaching method. Approximately 20 mg/ml (v/v) of the essential oils of M. alba was found to exhibit moderate antioxidant property (25% - 50%). Even though the essential oils was slow in its scavenging effects either with dichloromethane or pentane, the scavenging activity was independent of the solvent polarity. The oxidation of linoleic acid in - carotene bleaching test was best inhibited by the leaf extracted in dichloromethane (93.9%), compared to standard butylated hydroxytoluene (BHT) (83.3%). The antioxidant activity tested using the conjugated diene method showed higher inhibition of lipid peroxidation for both flower (PF: 90.7%) and leaf (PL: 77.1%) extracts in n-pentane, which was equivalent to the standard antioxidant, BHT (91.5%) and α-tocopherol (vitamin E) (77.2%). Overall, the essential oils from the flower showed slightly higher antioxidant activity than the leaf oils, both extracted in n-pentane. In order to ensure sustainability of the essential oils due to seasonal flowering problem, M. alba explants were induced for calli production for the corresponding secondary metabolites. Tepal, gynoecium, stamen and leaf explants were separately cultured on Murashige and Skoog (MS) and Woody Plant (WP) basal media each supplemented with various concentrations of NAA and kinetin in order to select the best medium for callus proliferation and organogenesis. Both media supplemented with phytohormones produced pale (colour) friable calli. However, the WPM medium produced remarkable callus proliferation compared to the MS medium with around 50% to 100% of the explants producing friable to compact nodular calli. Chemical compositions of the essential oils extracted with dichloromethane using simultaneous distillation extraction (SDE) from the callus cultures of gynoecium and stamen of M. alba flowers and analyzed by GC-MS revealed there were 60 peaks detected and approximately 15 compounds were identified in both oils. The compound with the highest composition in both essential oils was linalool with 50.0% in gynoecium oil and 28.8% in stamen oil for 0.1g of dry weight callus. The other abundant chemical components of gynoecium oil were β-elemen (10.0%), caryophyllene oxide (8.4%), caryophyllene (6.4%), germacrene D (4.2%), δ-cadinene (5.6%) and eugenol methyl ether (2.3%). The chemical constituents of stamen oil were α-bergamotene (12.5%), β-elemen (4.9%), germacrene-D (4.0%), δ- cadinene (4.8%), caryophyllene (3.4%) and caryophyllene oxide (2.9%). The major compounds of the essential oils from the callus cultures of gynoecium and stamen were not significantly different (p>0.05) from the essential oils of fresh gynoecium and stamen of M. alba flower. This study indicates that in vitro production of the oils via callus culture from gynoecium and stamen explants has potential in mass fragrance production from M. alba replacing the seasonal fresh flowers. In addition, the M. alba essential oils have the potentials as antimicrobial and antioxidant agents useful for the cosmetic industry.